Combining surface mechanical attrition treatment with friction stir processing to optimize the mechanical properties of a magnesium alloy - Zhang, Zhen (2020)
Friction stir processing (FSP) and surface mechanical attrition treatment (SMAT) were performed on an AZ31 magnesium alloy to improve the mechanical properties. The microstructure, macro-texture, as well as mechanical properties were investigated by optical microscopy, transmission electron microscopy, X-ray diffractometer and uniaxial tensile tests respectively. FSP significantly refined the initial grain structure and modified the texture of the experimental material; and the elongation got increased with a loss in yield and flow stresses. SMAT introduced a severely localized deformation layer on sample surfaces, which greatly strengthened the local micro-hardness and yield stress of parental matrix. By combining SMAT with FSP, the loss in yield and flow stresses caused by FSP could be well compensated by the SMAT routing. This optimized the mechanical properties of the experimental material.